Kelompok Usaha Bersama dan Perekonomian Masyarakat Dalam Pandangan Hukum Ekonomi Syariah - Agung Hermantono (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
The quality of Human Resources (HR) was something that was repeatedly emphasized by the president at the beginning of his second term. Strong and competitive Human Resources (HR) are the key to investment and an economy that continues to increase, the government in this case is fully concentrating on developing Human Resources (HR) (Interview with President Joko Widodo, quoted from BBC news Indonesia on 13 February 2020). Minister of Finance Sri Mulyani Indrawati said that the quality of human resources (HR) in the fields of sharia economics and finance needs to be improved, especially through the field of education. Currently there are 40,000 human resources (HR) in Indonesia who have competence in the field of sharia economics to work in this industry every year.